1992
DOI: 10.2307/2096099
|View full text |Cite
|
Sign up to set email alerts
|

Property Rights and Stratification in Socialist Redistributive Economies

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
125
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(129 citation statements)
references
References 40 publications
3
125
0
1
Order By: Relevance
“…Work units were largely responsible for the construction and the distribution of these housing units before the housing reform in the mid-1990s (Bian et al 1997;Logan and Bian 1993;Whyte and Parish 1984). The ownership and bureaucratic ranks of work units affected the size and the amenities of the housing units (Bian 1994;Walder 1986Walder , 1992.…”
Section: Post-reform Chinamentioning
confidence: 99%
“…Work units were largely responsible for the construction and the distribution of these housing units before the housing reform in the mid-1990s (Bian et al 1997;Logan and Bian 1993;Whyte and Parish 1984). The ownership and bureaucratic ranks of work units affected the size and the amenities of the housing units (Bian 1994;Walder 1986Walder , 1992.…”
Section: Post-reform Chinamentioning
confidence: 99%
“…Each work unit had a bureaucratic rank that supported its capacity to bargain with governments for resources on behalf of its employees. Work units constituted a hierarchy in which party/government institutions were ranked on the top and collectively-owned enterprises on the bottom (Brian 1994;Walder 1992). The strong dependence of workers on their work units and their identity became an important sign of social status and the main vehicle for social mobility (Lin & Bian, 1991;Wu, 2001).…”
Section: Urban Housing In Chinamentioning
confidence: 99%
“…Non-wage benefits from work Á/ larger and better housing in more desirable neighborhoods, access to better hospitals, use of vacation resorts, etc. (Voslensky 1980;Walder 1992) Á/ will influence actual income differences. Morrison (1984) estimated the advantages high-ranking CP members enjoyed in addition to their basic income and concluded that taking into account these non-wage benefits leads to greater income inequality.…”
Section: Data and Measuresmentioning
confidence: 99%